Упростить логическое выражение not(х1) * not (х2) * not (х3) + not(х1) * not (х2) * (х3 v not(х1) * (х2) * not(х3) v not(х1)* (х2) * (х3) v х1* not(х2) * not(х3) v (х1) * (х2) * not(х3) v х1 * х2 * х3

1

Ответы и объяснения

  • Sky09
  • профессор
2013-06-15T21:59:28+04:00

(¬x1*¬x2*¬x3)+(¬x1*¬x2*x3)+(¬x1*x2*¬x3)+(¬x1*x2*x3)+(x1*¬x2*¬x3)+(x1*x1*¬x3)(x1*x2*x3)=

=¬x1(¬x2*¬x3+¬x2*x3+x2*¬x3+x2*x3)+x1(¬x2*¬x3+x2*¬x3+x2*x3)=

=¬x1(¬x2(x3+¬x3)+x2(x3+¬x3))+x1(x2(x3+¬x3)+¬x2*¬x3)=

=¬x1(¬x2+x2)+x1(x2+¬x2*¬x3)=

=¬x1+x1(x2+¬x2*¬x3)